A Review on Flexible AC Transmission System Controllers (International Journal of Innovative Research in Engineering & Management, 2023)
Voltage stability has been a major concern  for operators in recent years, particularly for power system  that is highly loaded & have a reactive power deficit. The  voltage instability is a significant danger to the protection,  safety, and dependability of power systems. Due to limited  resources, power production and transmission development  has been insufficient in the past 10 years, even though  power consumption has risen considerably. As a result,  under high loads, existing transmission lines are utilized  near their thermal stability limitations, and system stability  becomes a power transfer limiting issue. Environmental,  political, social, and regulatory limitations prevent  significant development of generating and transmission  systems to meet increasing demand. Flexible Alternating  Current Transmission System (FACTS) controllers open the  way to improved power systems control, at least for the  transmissions line, in this context. FACTS technologies aids in the exploration of novel flow control options and  enhances the operating capabilities of current and future  transmission lines. This article provide a thorough  examination of the main FACTS controllers and their  applications.
Keywords: Electricity markets; FACTS controllers; Flexible ac transmission system; Power flow controL; Modern power systems; Power electronic; Power transmission